Kinerja Penyuluh Pertanian Dalam Pelaksanaan Administrasi Penyuluhan Pertanian - Andi Suprianto; Siti Aisa Lamane; Adi Rianto Suprayitno (Jurnal Sosial Ekonomi Pertanian, 2023)
Abstract The agricultural extension needs competencies related to intellectual skills (cognitive), skills related to psychology (affective), and physical movement skills (psychomotor). Farm extension workers must be able to respond quickly and effectively to existing farmer problems in the Industrial Age 4.0 so human resource preparedness is needed through collaboration between government, business, academics, community intellectuals, and agricultural extension agencies so that it is easy and there is upstream and downstream synergy. Of course, agricultural guidance in Palopo City is still much needed, as in other regions, even if they face the problem of narrow farming views, there will still be administrative problems that affect the success of their tasks in the field and office. This research aims to analyze the factors that influence the performance of agricultural extension workers in the city of Palopo. This survey was conducted in January 2023 at all Agricultural Extension Centers (BPP) in Palopo City. All 42 information officers with civil servant status were the samples in this study. The primary data collection technique was conducted through a survey method using a structured questionnaire. Analysis of research data through descriptive analysis using the Smart Partial Least Square (PLS) application. The results of the study show that age and seniority have a positive, direct, and significant effect on agricultural extension worker performance, knowledge of extension allowances and extension administration has a positive, direct, and significant effect on agricultural extension worker performance, the availability of office facilities and facilities for field activities have a positive and direct influence, but not significant, on the performance of agricultural extension Keywords: Administration of agricultural extension and extension services.